ANALISIS STRATEGI HUBUNGAN SEKOLAH DENGAN MASYARAKAT DALAM MENINGKATKAN MUTU PENDIDIKAN - jani sanjari (HASBUNA : Jurnal Pendidikan Islam, 2022)
This study aims to determine the activities of School Relations with the Community in improving the quality of education. The method used in this study uses a qualitative method. The results of this study indicate that as for the influencing factors of managerial Public relations in school institutions are very attached and varied, there must be what are called supporting and inhibiting factors, the supporting factor for this public relations program is the establishment of good communication relationships between parents, the community and the school, parental awareness of the importance of children's education and availability of funds for parents to support activities. The inhibiting factor is the uneven distribution of human resources in the community, which results in receiving information from public relations sometimes not being fully absorbed, resulting in misunderstandings, the misunderstanding, the community or parents do not directly ask the school which results in less participation, even though there are obstacles. still public relations continue to approach until the obstacles can be resolved with the best solution